2012
DOI: 10.1111/j.1464-410x.2011.10905.x
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib rechallenge in patients with metastatic renal cell carcinoma

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Targeted agents with a similar or different target molecule are often used sequentially in the treatment of metastatic RCC. Two tyrosine kinase inhibitors, sorafenib and sunitinib, have been reported to show little cross‐resistance, when used sequentially. In addition, a recent report showed that sunitinib rechallenge could potentially benefit selected patients. This case series shows that patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Postprogression survival, defined as the time between the last day of treatment and death or last visit recorded, has been demonstrated to strongly correlate with median OS [11,12]. Additionally, if there are more patients in the placebo/BSC arm who are intolerant to sorafenib but receive sorafenib rechallenge post-study treatment, those patients may benefit from sorafenib rechallenge after failure of study treatment, as has been reported in another study [13].…”
Section: Discussionmentioning
confidence: 68%
“…Postprogression survival, defined as the time between the last day of treatment and death or last visit recorded, has been demonstrated to strongly correlate with median OS [11,12]. Additionally, if there are more patients in the placebo/BSC arm who are intolerant to sorafenib but receive sorafenib rechallenge post-study treatment, those patients may benefit from sorafenib rechallenge after failure of study treatment, as has been reported in another study [13].…”
Section: Discussionmentioning
confidence: 68%
“…In another study of patients with metastatic RCC, stable disease was observed in six out of eight patients who originally discontinued sorafenib because of progressive disease and were then retreated with the same drug. 81 In these studies, antiangiogenic TKI rechallenge seems to have activity in RCC—and possibly in other malignancies, as observed in GIST case studies 82,83 —suggesting that resistance to sunitinib or sorafenib might be transient, at least in some individuals. 80 …”
Section: Rechallenge After Progression On Therapymentioning
confidence: 78%
“…In a case series of 12 patients who had failed first-line sorafenib and subsequent anti-VEGF therapies or mTOR inhibitors, eight (67%) achieved stable disease upon sorafenib rechallenge, with median PFS of 5.4 months [32]. In contrast to sunitinib rechallenge, the duration of PFS with sorafenib rechallenge did not correlate with the PFS duration observed with initial sorafenib treatment or with the length of the interval between initial treatment and rechallenge.…”
Section: Evidence For Rechallenge In Metastatic Renal-cell Carcinoma:mentioning
confidence: 84%
“…A summary of studies evaluating rechallenge either with agents from the same class or the same agent are provided in Table 2 [16,[29][30][31][32][33][34][35]. The majority of studies exploring rechallenge with the same agent have focused on sunitinib, and have been summarized in a recent review by Porta et al [14 && ].…”
Section: Evidence For Rechallenge In Metastatic Renal-cell Carcinoma:mentioning
confidence: 99%